2018
DOI: 10.3390/ijms19030918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mutations and Ligands on the Thermostability of the l-Arginine/Agmatine Antiporter AdiC and Deduced Insights into Ligand-Binding of Human l-Type Amino Acid Transporters

Abstract: Abstract:The L-arginine/agmatine transporter AdiC is a prokaryotic member of the SLC7 family, which enables pathogenic enterobacteria to survive the extremely acidic gastric environment. Wild-type AdiC from Escherichia coli, as well as its previously reported point mutants N22A and S26A, were overexpressed homologously and purified to homogeneity. A size-exclusion chromatographybased thermostability assay was used to determine the melting temperatures (T m s) of the purified AdiC variants in the absence and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
(97 reference statements)
1
16
0
Order By: Relevance
“…4 ). It has been proposed that Ser26 does not govern ligand selectivity through sidechain H bond interactions, since a fully transport-active AdiC S26A mutant shows a normal capacity to distinguish Arg + from Arg +2 11 , 30 . However experimental and theoretical studies, however, have shown that water molecules can, in some cases, take over the role of the mutated residue within the binding pocket 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…4 ). It has been proposed that Ser26 does not govern ligand selectivity through sidechain H bond interactions, since a fully transport-active AdiC S26A mutant shows a normal capacity to distinguish Arg + from Arg +2 11 , 30 . However experimental and theoretical studies, however, have shown that water molecules can, in some cases, take over the role of the mutated residue within the binding pocket 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…All of these bacterial transporters belong to the APC family, within the APC superfamily, and adopt the APC superfamily-fold, originally described for the bacterial transporter LeuT 24 . Structural models based on AdiC and ApcT have been used to obtain clues regarding substrate recognition by LAT1 25 and LAT2 16,26 . However, due to the low sequence identity with human LATs (14–22%) these models lack the robustness required to dissect the molecular mechanisms underlying transport, study the molecular defects associated with human mutations, and build structure-guided inhibitors with potential pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its biochemical and pharmacological interest, LAT1 structure has not been solved yet by crystallography. Some LAT1 comparative models have already been proposed, mostly based on the crystallographic structure of AdiC in the OF conformation (Dickens et al, 2013 ; Geier et al, 2013 ; Augustyn et al, 2016 ; Colas et al, 2016 ; Napolitano et al, 2017a ; Ilgü et al, 2018 ) which covers both the open and closed LAT1 conformations. However, since these models are all based on the only available OF conformation of different AdiC crystallographic structures, it is currently unknown which residues are actually involved in the substrate transport when LAT1 is in its IF conformation.…”
Section: Introductionmentioning
confidence: 99%